2017
DOI: 10.1159/000478970
|View full text |Cite
|
Sign up to set email alerts
|

Urgent-Start Peritoneal Dialysis: The First Year of Brazilian Experience

Abstract: Background: This study aimed to evaluate mechanical and infectious complications associated with urgent-start peritoneal dialysis (PD) and patients and technique survival in the first 180 days. Methods: It was a prospective study that evaluated chronic patients who started unplanned PD using high-volume PD (HVPD) right after (<72 h) PD catheter placement. After hospital discharge, patients were treated with intermittent PD on alternate days in a dialysis unit until family training was provided. Results: Fifty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 11 publications
1
15
0
1
Order By: Relevance
“…The results confirm that PD can be a safe method of introducing RRT in unplanned acute dialysis settings. In general they are comparable with those of other authors, presented in Table 9 (Song et al, 2000; Banli et al, 2005; Povlsen and Ivarsen, 2006; Jo et al, 2007; Lobbedez et al, 2008; Yang et al, 2011; Casaretto et al, 2012; Ghaffari, 2012; Koch et al, 2012; Masseur et al, 2014; Alkatheeri et al, 2016; Bitencourt Dias et al 2016, 2017; Jin et al, 2016; Pai et al, 2016; Wong et al, 2016; Xu et al, 2017; Wang et al, 2017; Nayak et al, 2018). However, there are many methodological differences among these studies concerning patients population, the technique of peritoneal catheter placement, or length of break-in period.…”
Section: Discussionsupporting
confidence: 91%
“…The results confirm that PD can be a safe method of introducing RRT in unplanned acute dialysis settings. In general they are comparable with those of other authors, presented in Table 9 (Song et al, 2000; Banli et al, 2005; Povlsen and Ivarsen, 2006; Jo et al, 2007; Lobbedez et al, 2008; Yang et al, 2011; Casaretto et al, 2012; Ghaffari, 2012; Koch et al, 2012; Masseur et al, 2014; Alkatheeri et al, 2016; Bitencourt Dias et al 2016, 2017; Jin et al, 2016; Pai et al, 2016; Wong et al, 2016; Xu et al, 2017; Wang et al, 2017; Nayak et al, 2018). However, there are many methodological differences among these studies concerning patients population, the technique of peritoneal catheter placement, or length of break-in period.…”
Section: Discussionsupporting
confidence: 91%
“…The most frequent short-term complication in patients who started PD urgently was catheter tip migration and leakage, as previously described by other studies. [10][11][12] The most common cause of patient dropout was transfer to HD for both groups (two patients in ES-PD and three in US-PD). The second most common cause of dropout was death with no difference between groups, as previously shown in investigations that compared US-PD with plannedstart PD (after 15 days of catheter insertion).…”
Section: Resultsmentioning
confidence: 99%
“…Several previous urgent-start PD studies have reported peri-catheter leaks ranging from 2% to 33%, depending on the catheter break-in time, insertion technique, fill volumes, and strategies to secure the deep cuff. 1 , 2 , 4 , 5 The relatively low rate in this Mexican study is impressive considering the very short break-in time and the quite high fill volumes, mostly 2 liters, initially used. In other urgent-start PD cohorts, the patients were given an incremental prescription with low fill volumes to reduce this risk, as described by Povlsen et al.…”
mentioning
confidence: 72%
“…Urgent-start PD has recently become popular in North America but it needs to be noted that it often involves a longer break-in period than reported in this and other studies from Brazil, Denmark, and Poland. 1 , 2 , 5 , 6 , 7 It is useful, as we have previously proposed, to subdivide urgent-start PD into truly “urgent-start” cases in which PD is initiated within 72 hours of catheter insertion, and less urgent ones in which the break-in period is between 3 and 14 days, which we have termed “early start PD.” 9 In “early start” PD, the whole process may be carried out without hospital admission and patients may be well enough to receive PD training in association with the early use of the catheter. An initial incremental approach with supine automated PD and low dwell volumes may be feasible, and risks of leak and other complications should be correspondingly less.…”
mentioning
confidence: 99%